ทำไม 3x ^ 2 + 3 / x ^ 2 = 3 (x + 1 / x) ^ 2-6?

ทำไม 3x ^ 2 + 3 / x ^ 2 = 3 (x + 1 / x) ^ 2-6?
Anonim

ตอบ:

ดูหลักฐานด้านล่าง

คำอธิบาย:

โดยใช้สูตรทวินาม

# (A + B) ^ 2 = a ^ 2 + 2AB + B ^ 2 #

เราได้รับ

# 3 (x ^ 2 + 1 / x ^ 2 + 2 * * * * * * * * x 1 / x) -6 = 3 (x ^ 2 + 1 / x ^ 2) + 6-6 = 3 (x ^ 2 + 1 / x ^ 2) #

ตอบ:

โปรดดูที่ด้านล่าง.

คำอธิบาย:

# 3x ^ 2 + 3 / x ^ 2 #

= # 3 (x ^ 2 + 1 / x ^ 2) #

= # 3 (x ^ 2 + 2 ×× x 1 / x + (1 / x) ^ 2-2 ×× x 1 / x) #

= # 3 ((x + 1 / x) ^ 2-2) #

= # 3 (x + 1 / x) ^ # 2-6

# 3 (x + 1 / x) ^ 2 - 6 #

# 3 (x ^ 2 + 1 / x ^ 2 + 2) -6 #

เปิดวงเล็บ

# 3x ^ 2 + 3 / x ^ 2 + 6-6 #

# 3x ^ 2 + 3 / x ^ 2 #